(untitled) - Boyes, William (Australia, 2014)
The supportive pedagogical framework that guides students through each chapter includes Fundamental Questions, which open and organize the chapter by focusing on three to six key issues, and which then reappear both at point of relevance in the margins and in the end-of-chapter Summary sections; Now You Try It checkpoint questions that quiz students on important concepts, with answers provided at the back of the book; Recaps at the end of each major section to break material into manageable segments; and end-of-chapter exercises that serve as self-checks for students and as homework assignment options for instructors
Keywords: Economics,Kinh tế